DEVELOPMENT OF A GUIDEBOOK ON BASIC MASSAGE TECHNIQUES FOR BEGINNERS FOR STUDENTS OF THE PHYSICAL AND PEDIGIC STUDY PROGRAM AT KARIMUN UNIVERSITY - Arief Fahmi; Rahmat Sanusi; Hari Adi Rahmad; Anggri Dwi Nata (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to produce a product, namely a massage guidebook for physical education students at Karimun University. This book can function as a medium to strengthen understanding of massage material. This study uses a research and development (R&D) method that refers to the 5 steps developed in ADDIE, namely analysis, planning, development, implementation, and evaluation. The population and sample used were 8 5th semester students at Karimun University. The instrument was a questionnaire. Data analysis techniques used qualitative and quantitative descriptive. The average value for the validation criteria used the percentage of assessment scores. The validation results from material experts obtained a score of 92% with a very good description. The validation results from media experts obtained a score of 88% with a very good description. The results of the lecturer's response obtained a score of 98% with a very good description. There is a very significant influence of the use of the massage guidebook on students' understanding of massage in the knowledge or written test with the results of the t-test of 3.693 greater than the t-table value (1.860). There was also a significant effect of using a massage guidebook on students' understanding of massage in the practical test, with a t-test result of 2.740, greater than the t-table value (1.860).